Analysis Of Higher Order Thinking Skill (Hots) Problems In Student's Books Theme 3 Class V Elementary School - Sarah Fazilla; Fauziana Fauziana; Paridah Hanum Siregar (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
The lack of Higher Order Thinking Skills (HOTS) questions in student books causes students to receive inadequate training in solving such questions. This has resulted in the failure to achieve the goals of the 2013 curriculum's learning program, which aimed to equip students with Higher Thinking Skills and 21st-century skills. Therefore, it is important to conduct an analysis of the questions in Class V Student Book Theme 3, "Healthy Food," as higher-order thinking skills must be nurtured through the use of questions that align with the HOTS level. This study aims to determine whether the questions in the Class V Student Book Theme 3, "Healthy Food," published by the Ministry of Education and Culture in 2017, qualify as HOTS questions. Additionally, it seeks to assess the quality of these HOTS questions in the Student Book for Class V Theme 3, "Healthy Food," published by the Ministry of Education and Culture in 2017. The method employed in this study is content analysis. The data analysis in this study was conducted qualitatively, involving the examination of document data—specifically, the questions in the Class V Student Book Theme 3, "Healthy Food." These questions were categorized according to Bloom's Taxonomy levels, ranging from C1 to C6. The analysis results are presented as percentages for each question type. The subject of this study was the Class V Student Book Theme 3, "Healthy Food," published by the Ministry of Education and Culture in 2017, which encompassed four sub-themes. Documentation was the chosen technique and tool for data collection in this study. The research findings revealed that: at the analyzing level (C4), the items constituted 35.2%; at the evaluating level (C5), the items comprised 23.5%; and at the creating level (C6), the items constituted 76.4%. As a result, the quality of the questions in the Class V Student Book Theme 3, "Healthy Food," indicates that a significant majority, 76.4% of the questions, are centered around the creation level.